Adverse Events in Breast Cancer Patients Receiving Adjuvant Endocrine Therapy: Frequency and Related Factors - Thi Hong Hanh, Nguyen; Thi Thu Trang, Tran; Thi Minh Chi, Nguyen; Khanh Linh, Duong; Hoang Long, Nguyen; Quang Toan, Phung; Thi Le Hao, Hoang; Thi Lien Huong, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
A cross-sectional study was conducted on 863 outpatients at two oncology hospitals in Hanoi from January 2020 to July 2020 who had been prescribed tamoxifen or aromatase inhibitors (AIs) for at least 3 months before data collection. Patients reported adverse events (ADEs) experienced within the last 4 weeks and their severity based on Likert scale from 1 to 4. Patients in the study group had a mean age of 53.6 years; min-max 25 - 81 years, menopausal rate of 88.2%, were mainly in stage 2 (57.6%), and were treated with aromatase inhibitors (56.6%). A large proportion of patients experienced adverse events in the nervous system (63.7%) and the musculoskeletal system (71.1%). The most common symptoms were arthralgia (59.6%), sleep disturbance (52.8%), and hot flashes (45.3%). Most patients reported grade 1 and 2 events. Patients using AIs had an increased risk of experiencing musculoskeletal adverse events (OR 1.58, 95%CI 1.12-2.21). Patients who had received chemotherapy had a higher probability of fatigue (OR 1.56, 95%CI 1.00-2.42). Patients younger than 50 years old were more likely to have ADEs of the reproductive system, hot flashes, neurologic ADEs, and fatigue. Patients with comorbidities had a statistically significant increased risk of most self-reported ADEs. Measures to raise awareness and manage ADEs in cancer patients using adjuvant endocrine therapy are recommended, especially for patients with multiple risk factors.